Workshop Cara Cerdas Pemilihan Produk Suplemen Herbal dalam E-Commerce kepada Mahasiswa Prodi Farmasi STIKes Abdurahman Palembang - Maiza Fikri; Hendra Prasetyo; Januar Ida Wibowati; Hendriansyah Hendriansyah; Faridatul Munawaroh; Nita Novianti (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2026)
The phenomenon of increasing herbal supplement purchases through e-commerce platforms presents new challenges for pharmacy students in understanding product safety and legality within the digital space. As future healthcare professionals, students are required to possess the acuity to verify products to prevent health risks for the public. This Community Service Program (PKM) aims to improve students' pharmaceutical digital literacy through an interactive workshop on smart strategies for selecting safe and legal herbal supplement products. The implementation methods included lectures, focus group discussions, and case studies utilizing authentic learning media such as product labels, BPOM permit verification, health claim analysis, and critical assessment of consumer reviews. The program's success was evaluated through pre-test and post-test instruments to quantitatively measure the improvement in participants' knowledge. The results indicated a significant increase in understanding by 33%, particularly in the ability to identify legal products, analyze claim accuracy, and optimize digital literacy features. In conclusion, this workshop has a positive and strategic impact on students' readiness to face digital pharmacy challenges in the Industry 4.0 era, while simultaneously preparing them to serve as education agents for the wider community.